2018
DOI: 10.1016/j.rmed.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung abnormality is prevalent and associated with worse outcome in patients undergoing transcatheter aortic valve replacement

Abstract: ILA is a common finding among patients with severe AS and is associated with increased mortality in those undergoing TAVR. Further research is needed to elucidate the biology underpinning this observation and determine whether ILA evaluation and risk stratification modulates this mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…4,21 Furthermore, patients with ILA appear to have a worse prognosis than those without. 4,7 A recent study examining lung cancer resection specimens identified histopathologic findings of subpleural fibrosis and fibroblastic foci in subjects with radiological ILA. 22 These findings add weight to the possibility that minor ILA represent pre-clinical fibrotic lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,21 Furthermore, patients with ILA appear to have a worse prognosis than those without. 4,7 A recent study examining lung cancer resection specimens identified histopathologic findings of subpleural fibrosis and fibroblastic foci in subjects with radiological ILA. 22 These findings add weight to the possibility that minor ILA represent pre-clinical fibrotic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the significance of ILA is not clearly defined, studies have found associated decrements in exercise capacity, reduced health and functional status, decline in lung function and increased risk of all-cause mortality and pulmonary fibrosis specific mortality. [4][5][6][7][8][9] Detection of ILA in populations receiving CT scans for other reasons may provide much needed insights into the natural history of fibrotic lung disease and inform the discussion about indications for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to one singlecenter study, which assessed pre-TAVR high-resolution computed tomography scans in 623 patients who underwent TAVR, interstitial lung abnormality (which also included a quarter of patients with a diagnosis of IPF) was prevalent in 14.7% of the cases and was an independent predictor of mortality in patients undergoing TAVR. 17 In contrast, a recent study utilizing the Nationwide Inpatient Sample database from 2011 to 2014 found that respiratory complications such as need for tracheostomy (0.8% vs 5.8%), acute respiratory failure (16.4% vs 23.7%), reintubation (6.5% vs 10%), and pneumonia (4.5% vs 10.1%) were significantly less frequent with TAVR vs SAVR for COPD patients. 18 Extrapolating these findings to our study, we found that in ILD patients, TAVR resulted in a superior perioperative outcome from a respiratory standpoint, resulting in shorter ventilation times (approximately 3 hours less), less ICU requirement (less than half the time), and clinically lower rates of reintubation (1.9% vs 2.7%) and prolonged ventilation (3.8% vs 8.1%).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, there are no contemporary studies that have specifically examined the impact of ILD and IPF in patients with AS per se, which is important because choosing a particular approach (either SAVR or TAVR) remains one of the biggest challenges for clinicians and an impetus for this study. According to one single‐center study, which assessed pre‐TAVR high‐resolution computed tomography scans in 623 patients who underwent TAVR, interstitial lung abnormality (which also included a quarter of patients with a diagnosis of IPF) was prevalent in 14.7% of the cases and was an independent predictor of mortality in patients undergoing TAVR . In contrast, a recent study utilizing the Nationwide Inpatient Sample database from 2011 to 2014 found that respiratory complications such as need for tracheostomy (0.8% vs 5.8%), acute respiratory failure (16.4% vs 23.7%), reintubation (6.5% vs 10%), and pneumonia (4.5% vs 10.1%) were significantly less frequent with TAVR vs SAVR for COPD patients .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of periprocedural IPF exacerbation was reported to be 0.4% among patients undergoing TAVI [4]. It is important to focus on specific populations with a baseline interstitial lung abnormality, which was found in 14.7% of those referred for TAVI [5]. These data suggest that IPF exacerbation will occur in 2-3% of TAVI cases with a baseline interstitial lung abnormality.…”
Section: Discussionmentioning
confidence: 95%